Tindak Tutur Ibu Dan Anak Dalam Film Keluarga Susah Sinyal - Ayu Aprilia Gayatri, Ni Made; Sosiowati, IGAG (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): : September, 2020)
This article aims to find out the types and functions of speech acts of mother and child contained in the family movie with the title Susah Sinyal . This study uses a qualitative approach. The method of data collection used is the method of listening with a free and involved way of reading and note taking techniques. The data source in this study is in the form of speech by mother and child in the family movie with the title Susah Sinyal . The results showed that mother and child speech acts in the family movie with the title Susah Sinyal can be classified based on the type and function of speech acts. In terms of the types of speech acts that are found include: locutionary act, illocutionary act and perlocutionary act. Meanwhile, in terms of speech act functions found include: assertive, directive, expressive, commissive and declarative.